Empreendedorismo teuto-rio-grandense : o caso das empresas Bromberg & CIA. (1860–1932) - Machado, Janete da Rocha (2019)
The present investigation aimed to analyze the construction and development of the Bromberg family business that took place in southern South America from 1860 to 1932. Bromberg & Cia., Together with other German enterprises, have in the past integrated the high trade teuto-rio-grandense in Brazil. The capitalist conception and the entrepreneurial spirit of some groups, coming from more developed regions of Germany like the city of Hamburg, were fundamental for the emergence of the first industries in the state. Through the import trade and the consequent process of industrialization, these entrepreneurs collaborated in the historical modernization in the late nineteenth and early twentieth century in Rio Grande do Sul. The thesis also investigated the trajectory of Martin Bromberg, the first of the family to come to Brazil, and founder of Bromberg & Cia, one of the largest distributors of German machinery throughout South America.